A novel Bacillus thuringiensis isolate toxic to cotton pink bollworm (Pectinophora gossypiella Saunders). (January 2021) - Reyaz, A.L.; Balakrishnan, N.; Udayasuriyan, V.
Abstract: In this study, we report a novel indigenous Bacillus thuringiensis ( Bt ) isolate, T26, which showed spores and crystals under scanning electron microscope and pathogenicity against the pink bollworm ( Pectinophora gossypiella Saunders) in artificial diet based bioassay. SDS-PAGE analysis of the spore-crystal mixture of the Bt isolate, T26 revealed presence of three major protein bands of approximate molecular weights of 80, 55 and 40 kDa. The draft genome assembly consists of 56 scaffolds with an entire draft genome size of 5, 054, 095 bp. NCBI blast analysis revealed that assembled draft genome is spread over in a chromosome (4, 818, 543 bp) and one plasmid (235, 552 bp). NCBI Prokaryotic Genome Annotation Pipeline (PGAP) showed presence of 5033 coding gene sequences and 159 RNAs genes. None of the known lepidopteran active genes ( cry 1, cry 2 and cry 9) could be detected with PCR or with whole genome sequence analysis using Bt toxin scanner tool or CryProcessor tool. Thus, presence of protein crystals and toxicity towards cotton pink bollworm and absence of any known cry / vip / cyt type of genes in draft genome indicates it is a novel type of Bt isolate. Further investigation of this genome sequence along with protein sequencing will lead to understand the novel factors responsible for its virulence and could be a useful tool for the insect resistance management in pink bollworm. Graphical abstract: Image 1 Highlights: Bacillus thuringiensis isolate T26 showed spores and crystals under microscope and pathogenicity against the pink bollworm. SDS-PAGE analysis of the spore-crystal mixture revealed presence of major protein bands with ~ 80, 55 and 40 kDa sizes. None of the known lepidopteran active genes could be detected with PCR or with whole genome sequence analysis.